Incomplete functional and morphological recovery after acute and acute recurrent pancreatitis in children. Issue 1 (28th June 2018) - Puttaiah Kadyada, Srikanth; Thapa, Babu Ram; Kaushal, Karanvir; Walia, Rama; Rana, S V; Dhaka, Narendra; Lal, Sadhna B; Prasad, Rajendra; Das, Subhamoy; Thakur, Rajini; Kamal, Kishore
Abstract: Background and Aim: There is lack of data on functional and morphological recovery after an attack of acute pancreatitis (AP) or acute recurrent pancreatitis (ARP) in children. This study aims to evaluate the functional impairment and morphological changes in the pancreas after recovery. Methods: All consecutive patients presenting with AP ( n = 61) or ARP ( n = 35), as per standard diagnostic criteria, were enrolled. After 2 months of pancreatitis, fecal elastase‐1 (FE‐1) (μg/g) and 2‐h oral glucose tolerance test to calculate oral disposition index (DIo ) (mmol/L) (β‐cell function) were performed. Morphological changes were assessed by endoscopic ultrasound and transabdominal ultrasound. Patients with chronic pancreatitis (CP) ( n = 27) and healthy children (HC) ( n = 26) were included as controls for functional parameters. Results: At a median follow up of 12 (4–44) and 11 (2–108) months, 66.7% and 75.9% ( P = 0.57) of AP and ARP demonstrated exocrine insufficiency (FE‐1 < 200), respectively. Mean (SD) FE‐1 was 183.64 ± 150.94 (AP), 135.70 ± 103.80 (ARP), 46.56 ± 30.20 (CP), and 240.00 ± 181.83 (HC) ( P < 0.001;anova ) (AP vs CP, ARP vs CP, and CP vs HC; P < 0.001). Prediabetes due to insulin resistance was seen in 16.6% and 22.6% ( P = 0.56) of AP and ARP. Median (interquartile range) DIo (mmol/L) was comparable between AP (4.20 [2.36, 8.3]) and HC (5.20 [2.89, 8.68]), but was low in ARP (2.97 [1.80, 5.12]), which was comparable with CP (1.91 [1.20, 2.83]). Endoscopic ultrasound demonstrated morphological changes in 25% and 37% ( P = 0.34) of AP and ARP, respectively. Conclusion: There was high frequency of biochemical evidence of exocrine insufficiency. β‐Cell function (DIo ) was preserved among AP but was poor in ARP. Nearly one‐third showed morphological changes in imaging.